Peranan Organisasi Al Jamiatul Wasliyah Cabang Tanah Karo Tahun 1938-1967 - Abdul Halim Simamora; Trisni Andayani (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political Social UMA), 2016)
This study aims to find out the history of establishment of the Organization of Al Jamiatul Washliyah in Tanah Karo In the year 1938-1967. To know the efforts and role of Al Jamiatul Washliyah in Advancing Education in Tanah Karo. To know that in the Education Process Holds Al Jamiatul Washliyah in Tanah Karo. To obtain the data conducted field research with qualitative descriptive type in Tanah Karo Karo District of Kabanjahe. Data obtained by observation and interview, the informant who qditentukan with purposive sampling. Al Jamiatul Washliyah is an organization engaged in education, propaganda, social and economic empowerment charity keumatan. Doctrine Al Jamiatul Wasliyah entered Karo with the aim to broadcast the Islamic religion sent by the Malay sultanate and the invitation of Islamic preachers to pengislamisasian Tanah Karo Karo people and provide teaching about the true meaning of Islam. Once received by the Karo people, the organization Al Jamiatul Washliyah inaugurated in 1938 in Berastagi initially and so on set in Kabanjahe with the leadership of H. Bahrum Lubis. Until now, the organization Al Jamiatul Washliyah standing and growing. Based on the results of the research findings can be concluded that with the establishment and involvement of the Al Jamiatul Wasliyah in Kabanjahe has helped broadcast the Islamic religion and education in Kabanjahe.